Laminating ink composition for flexible packaging
By using polyester resin and chlorinated polyolefin resin as binder resin in liquid ink for flexible packaging lamination, the viscosity and solvent content of the ink are optimized, and the problem of insufficient performance of existing inks on diversified packaging substrates is solved. , achieving high lamination adaptability, adhesion resistance and printing adaptability.
Patent Information
- Application Number
- CN202280097802.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-08-04
- Filing Date
- 2022-11-10
- Publication Date
- 2025-02-21
AI Technical Summary
The existing liquid ink for flexible packaging lamination shows insufficient adhesion, adhesion resistance and polyethylene extrusion lamination strength on diverse packaging substrates, and the high solvent volatility makes it difficult to meet the diversity of modern packaging materials' performance. Demand.
Using a liquid ink composition containing polyester resin and chlorinated polyolefin resin as binder resin, the ink is optimized by adjusting the molecular weight, hydroxyl value and chlorination of the resin, combined with other resins such as vinyl chloride-vinyl acetate copolymer resin. viscosity and solvent content.
High-concentration liquid ink with low viscosity and low solvent content is achieved, which significantly improves lamination adaptability, adhesion resistance and printing adaptability on various films, and meets the diversified performance needs of modern packaging materials.
Smart Images

Figure BDA0005225496780000281 
Figure BDA0005225496780000291 
Figure BDA0005225496780000301
Abstract
Description
Technical Field
[0001] The present invention relates to a liquid ink composition for flexible packaging lamination, and more particularly to a liquid ink composition for flexible packaging lamination, which is a lamination gravure ink or flexographic ink that can exhibit very excellent adhesion performance on a printed laminated substrate, and is used for various films coated with various polyolefin films, polyester films, polyamide films, and inorganic and organic barrier coating materials. Background Art
[0002] Gravure inks and flexographic inks are widely used for the purpose of imparting beauty and functionality to printed materials. When printed materials after gravure or flexographic printing are used in packaging materials, especially as food packaging materials, lamination is usually performed. In this case, various printed materials and lamination processes are used depending on the type of content and the purpose of use.
[0003] In the past, in such laminated products, printing inks with polyurethane resin as a binder have excellent adhesion to various printed bodies, lamination strength of various laminated products, and boil retort adaptability, so they are widely used. For example, Patent Document 1 discloses a laminated printing ink composition with a polyurethane polyurea resin soluble in an organic solvent as the main binder resin, and the polyurethane polyurea resin is obtained by reacting a polymer diol, an organic diisocyanate, and a diamine as a chain extender. Then, various studies have been conducted to improve the physical properties of the laminate. Patent Document 2 illustrates that in a polyurethane resin obtained from a polymer diol and an organic diisocyanate, a polyester polyol obtained from 3-methyl-1,5-pentanediol and a dibasic acid is used as a polymer diol compound to improve adhesion, hydrolysis resistance, and resolubility.
[0004] In addition, Patent Documents 3 and 4 illustrate that the use of a polyurethane resin obtained by reacting a specific diol component with an organic diisocyanate and an amine-based chain extender can improve adhesion, resolubility, printability, etc., and various studies have been conducted to improve satisfactory lamination strength and printability.
[0005] However, with the diversification of packaging substrates in recent years, high performance is required for printing inks used for decoration or surface protection, and the current situation is that the laminating ink of the above invention is not fully satisfactory. From the market point of view, in order to make a single material, regardless of the type of film, it is required to improve the extrusion lamination strength, improve the lamination strength before and after boiling treatment on various substrates, and also to improve the level of the film coated with the above inorganic and organic barrier coating agents.
[0006] Furthermore, the ink obtained from these polyurethane resins and organic solvents has high viscosity and the amount of solvent in the ink blend during actual printing is large. In recent years, from the perspective of environment and hygiene, it is required to reduce the amount of solvent volatilization on the printing press. In addition, in order to reduce the amount of solvent volatilization, there is a tendency to use a lighter version than before, and in the past ink using polyurethane resin, it is also difficult to show the printing density under the condition of reducing the coating amount.
[0007] Furthermore, when a low-viscosity polyurethane resin is used to reduce the viscosity of the ink, the ink tends to have poor blocking resistance, boiling resistance, resistance to contents, polyethylene extrusion lamination strength, printability, etc., and it is difficult to satisfy all of these properties in accordance with market requirements.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent Application Laid-Open No. 55-25453
[0011] Patent Document 2: Japanese Patent Application Laid-Open No. 63-161065
[0012] Patent Document 3: Japanese Patent Application Laid-Open No. 6-80921
[0013] Patent Document 4: Japanese Patent Application Laid-Open No. 11-279472 Summary of the invention
[0014] Problems to be solved by the invention
[0015] An object of the present invention is to provide a liquid ink composition which is applicable to a wide range of types of films and has excellent adhesion, anti-blocking properties and polyethylene extrusion lamination strength to various substrates.
[0016] Methods for solving problems
[0017] The present inventors have conducted intensive studies to solve the above-mentioned problems and have found that it is effective to solve the problems by including a polyester resin and a chlorinated polyolefin resin as a binder resin in a liquid ink composition.
[0018] That is, the present invention relates to a liquid ink composition characterized in that the binder resin contains a polyester resin (A) having a number average molecular weight within a range of 500 to 20,000 and a chlorinated polyolefin resin (B) as essential components.
[0019] The present invention also relates to a liquid ink composition, wherein the polyester resin (A) has a hydroxyl value in the range of 10 to 150 mgKOH / g, more preferably 20 to 60 mgKOH / g.
[0020] The present invention also relates to a liquid ink composition, wherein the polyolefin resin (B) has a weight average molecular weight of 10,000 to 60,000 and a degree of chlorination of 10% or more.
[0021] The present invention also relates to a liquid ink composition comprising another resin having a glass transition temperature of 40° C. or higher as a component other than the polyester resin (A) and the chlorinated polyolefin resin (B).
[0022] Furthermore, the present invention relates to a printed article and a laminated article obtained by printing the liquid ink composition.
[0023] Effects of the Invention
[0024] According to the present invention, a liquid ink composition with low viscosity and low solvent content and high concentration can be obtained. Therefore, the amount of solvent volatilization can be reduced, which is suitable for the environment and hygiene, and a shallower plate than before can be used, so that excellent printing adaptability can be achieved with a smaller coating amount than before. In addition, according to the present invention, a liquid ink composition with excellent lamination adaptability and anti-blocking properties on a wide range of films can be obtained. The liquid ink composition of the present invention can be suitably used as a laminated ink composition for flexible packaging. DETAILED DESCRIPTION
[0025] The present invention will be described in detail. It should be noted that the "ink" used in the following description all means "printing ink". In addition, "parts" all mean "parts by weight". "Total ink amount" means the total amount of all inks including volatile components such as organic solvents, and "total ink solid content" means the total amount of only non-volatile components excluding volatile components.
[0026] In addition, in the present invention, the liquid printing ink refers to a liquid ink suitable for a printing method using a printing plate, such as a gravure ink or a flexographic ink, and is preferably a gravure ink or a flexographic ink. In addition, the liquid printing ink of the present invention does not contain an active energy curable component, that is, it is a liquid ink that is not reactive to active energy rays.
[0027] The present invention provides a liquid ink composition, characterized by containing a polyester resin and a chlorinated polyolefin resin as a binder resin.
[0028] The liquid ink composition of the present invention is specifically prepared by premixing a binder resin containing the polyester resin (A) and the chlorinated polyolefin resin (B) in various organic solvents such as ethyl acetate, methyl ethyl ketone, toluene, and IPA, and various additives. While stirring the solution with a dispersing stirrer, a coloring pigment is added and further kneaded to obtain an ink composition in which the coloring pigment is fully dispersed. Alternatively, the binder resin containing the polyester resin (A) and the chlorinated polyolefin resin (B) is mixed with various organic solvents such as ethyl acetate, methyl ethyl ketone, toluene, and IPA, and various additives in a pigment dispersion in which the pigment is pre-dispersed to obtain an ink composition.
[0029] (Polyester resin (A))
[0030] The number average molecular weight of the polyester resin (A) used in the liquid ink composition of the present invention is within the range of 500 to 20,000.
[0031] If the number average molecular weight of the polyester resin (A) used in the liquid ink composition of the present invention is less than 500, the anti-blocking property tends to be poor, and if it is more than 20,000, the re-dissolution property and viscosity stability are poor.
[0032] As the polyester resin (A) used in the liquid ink composition of the present invention, various known polyesters can be used, and one type or two or more types can be used in combination.
[0033] The polyester resin is preferably a resin obtained by dehydration condensation or polymerization of a polyol and a polycarboxylic acid or a polycarboxylic acid anhydride.
[0034] Examples of the polyol include saturated or unsaturated low molecular weight polyols such as ethylene glycol, 1,2-propylene glycol, 1,3-propylene glycol, 2-methyl-1,3-propylene glycol, 2-ethyl-2-butyl-1,3-propylene glycol, 1,3-butanediol, 1,4-butanediol, neopentyl glycol, pentanediol, 3-methyl-1,5-pentanediol, hexanediol, octanediol, 1,4-butynediol, 1,4-butanediol, diethylene glycol, triethylene glycol, dipropylene glycol, glycerol, trimethylolpropane, trimethylolethane, 1,2,6-hexanetriol, 1,2,4-butanetriol, sorbitol, and pentaerythritol.
[0035] Examples of the polycarboxylic acid include adipic acid, phthalic acid, isophthalic acid, terephthalic acid, maleic acid, fumaric acid, succinic acid, oxalic acid, malonic acid, glutaric acid, pimelic acid, suberic acid, azelaic acid, sebacic acid, trimellitic acid, and pyromellitic acid. Anhydrides of these acids may also be used.
[0036] As the polyester, there can be used those obtained by ring-opening polymerization of cyclic ester compounds, for example, lactones such as polycaprolactone, polyvalerolactone, and poly(β-methyl-γ-valerolactone).
[0037] The polyester resin of the present invention is not particularly limited in its production method and can be produced by any method. Specifically, all the reaction raw materials can be reacted together, or a part of the reaction raw materials can be added in batches. The reaction temperature is preferably about 180 to 300° C., similar to the reaction temperature of a general polyester resin, and a known and commonly used esterification catalyst can be used as needed.
[0038] The number average molecular weight of the polyester resin (A) is preferably in the range of 500 to 20,000, more preferably in the range of 800 to 15,000, and more preferably in the range of 1,000 to 10,000.
[0039] In addition, the number average molecular weight of the said polyester resin shows the value measured by the gel permeation chromatography (GPC) method under the following conditions.
[0040] Measuring device: High-speed GPC device ("HLC-8220GPC" manufactured by Tosoh Corporation)
[0041] Column: The following columns manufactured by Tosoh Corporation were connected in series and used.
[0042] "TSKgel G5000" (7.8mm I.D. × 30cm) × 1 piece
[0043] "TSKgel G4000" (7.8mm I.D. × 30cm) × 1 piece
[0044] "TSKgel G3000" (7.8mm I.D. × 30cm) × 1 piece
[0045] "TSKgel G2000" (7.8mm I.D. × 30cm) × 1 piece
[0046] Detector: RI (differential refractometer)
[0047] Column temperature: 40°C
[0048] Eluent: Tetrahydrofuran (THF)
[0049] Flow rate: 1.0mL / min
[0050] Injection volume: 100 μL (tetrahydrofuran solution with a sample concentration of 0.4 mass%)
[0051] Standard samples: The following standard polystyrene was used to prepare a calibration curve.
[0052] (Standard Polystyrene)
[0053] "TSKgel Standard Polystyrene A-500" manufactured by Tosoh Corporation
[0054] "TSKgel Standard Polystyrene A-1000" manufactured by Tosoh Corporation
[0055] "TSKgel Standard Polystyrene A-2500" manufactured by Tosoh Corporation
[0056] "TSKgel Standard Polystyrene A-5000" manufactured by Tosoh Corporation
[0057] "TSKgel Standard Polystyrene F-1" manufactured by Tosoh Corporation
[0058] "TSKgel Standard Polystyrene F-2" manufactured by Tosoh Corporation
[0059] "TSKgel Standard Polystyrene F-4" manufactured by Tosoh Corporation
[0060] "TSKgel Standard Polystyrene F-10" manufactured by Tosoh Corporation
[0061] "TSKgel Standard Polystyrene F-20" manufactured by Tosoh Corporation
[0062] "TSKgel Standard Polystyrene F-40" manufactured by Tosoh Corporation
[0063] "TSKgel Standard Polystyrene F-80" manufactured by Tosoh Corporation
[0064] "TSKgel Standard Polystyrene F-128" manufactured by Tosoh Corporation
[0065] "TSKgel Standard Polystyrene F-288" manufactured by Tosoh Corporation
[0066] "TSKgel Standard Polystyrene F-550" manufactured by Tosoh Corporation
[0067] The hydroxyl value of the polyester resin (A) is preferably in the range of 10 to 150 mgKOH / g, more preferably 20 to 60 mgKOH / g.
[0068] The acid value of the polyester resin (A) is preferably in the range of 0 to 100 mgKOH / g, more preferably 0 to 50 mgKOH / g.
[0069] Furthermore, the polyester resin (A) is preferably contained in an amount of 30% by mass or more, more preferably 40% by mass or more, and even more preferably 50% by mass or more in terms of solid content relative to 100% by mass of the binder resin solid content.
[0070] (Chlorinated polyolefin resin (B))
[0071] The liquid ink composition of the present invention contains a chlorinated polyolefin resin (B). By containing the chlorinated polyolefin resin, the adhesion of the liquid printing ink to the treated or untreated substrate film can be improved. Among them, excellent adhesion can be obtained even for polyolefin films whose adhesion is easily deteriorated, so excellent adhesion can be achieved regardless of the type of film.
[0072] The chlorinated polyolefin resin can use various known chlorinated polyolefin resins, preferably dissolved in an organic solvent. The structure of the polyolefin resin in the chlorinated polyolefin resin is not particularly limited. For example, it is preferably a resin containing a homopolymer or copolymer of an α-olefin unsaturated hydrocarbon such as polypropylene, poly-1-butene, poly-4-methyl-1-pentene, etc. Among them, a resin containing a polypropylene structure (i.e., a chlorinated polypropylene structure) is particularly preferred.
[0073] The chlorinated polyolefin resin may be a modified product. The modified product is not particularly limited. For example, the modified product of the chlorinated polyolefin is a modified product in which a polymerizable acrylic compound (acrylic acid, methacrylic acid or their alkyl esters, etc.) or an unsaturated polycarboxylic acid (maleic acid, maleic anhydride, itaconic acid, itaconic anhydride, etc.) is graft-polymerized on the chlorinated polyolefin, or a modified product in which the polyolefin graft-polymerized with the above unsaturated polycarboxylic acid is chlorinated.
[0074] The degree of chlorination of the chlorinated polyolefin resin (B) is preferably 10% to 60%, more preferably 20% to 55%, and even more preferably 30% to 50%. When the degree of chlorination is less than 10%, the solubility of the chlorinated polyolefin resin in the solvent tends to be easily reduced. On the other hand, when the degree of chlorination is greater than 60%, the adhesion of the liquid printing ink to a substrate film such as polyethylene and polypropylene tends to be easily reduced. By setting the degree of chlorination within the above range, the liquid printing ink can exhibit excellent adhesion to various films.
[0075] The weight average molecular weight of the chlorinated polyolefin resin (B) is preferably 10000 to 60000, more preferably 11000 to 50000, and even more preferably 12000 to 30000. A weight average molecular weight of 60000 or less is preferred because compatibility can be improved.
[0076] The content of the chlorinated polyolefin resin is preferably 0.01% by mass to 10% by mass, preferably 0.05% by mass to 8% by mass, and more preferably 0.01% by mass to 5% by mass, based on the total amount of the liquid printing ink.
[0077] The solid content ratio of the polyester resin (A) to the chlorinated polyolefin (B) is preferably in the range of 100:0.1 to 100:30.
[0078] (Other combined resins)
[0079] Examples of auxiliary resins used in the liquid ink composition of the present invention as needed include resins other than the above-mentioned polyester resins and chlorinated polyolefin resins, such as vinyl chloride-vinyl acetate copolymer resins, ethylene-vinyl acetate copolymer resins, vinyl acetate resins, polyurethane resins, polyurethane urea resins, alkyd resins, polyvinyl chloride resins, rosin resins, rosin ester resins, ketone resins, cyclized rubber, chlorinated rubber, petroleum resins, rosin, etc. The auxiliary resins used in combination may be used alone or in combination of two or more. The content of the auxiliary resins used in combination is preferably 1 to 20% by weight, more preferably 2 to 15% by weight, relative to the total weight of the ink.
[0080] As the combined resin, it is preferable to contain other resin components having a glass transition temperature of 40° C. or higher.
[0081] (Other resin components having a glass transition temperature of 40°C or higher)
[0082] The liquid ink composition of the present invention preferably contains another resin component having a glass transition temperature of 40° C. or higher. By adding another resin component having a glass transition temperature of 40° C. or higher, the anti-blocking property is further improved.
[0083] Examples of other resins having a glass transition temperature of 40° C. or higher include vinyl chloride-vinyl acetate copolymer resins, polyamide resins, acrylic resins, nitrocellulose, cellulose acetate propionate, cellulose acetate butyrate, ketone resins, and butyral resins.
[0084] As other resin having a glass transition temperature of 40° C. or higher, it is preferable to use a vinyl chloride-vinyl acetate copolymer resin in order to further improve the retort resistance.
[0085] The vinyl chloride-vinyl acetate copolymer resin is preferably a vinyl chloride-vinyl acetate copolymer resin having a hydroxyl group, preferably having a hydroxyl value of 50 to 200 mgKOH / g, and containing 80 to 95% by weight of the vinyl chloride component in the copolymer resin.
[0086] The vinyl chloride-vinyl acetate copolymer resin having hydroxyl groups can be obtained by two methods. One is to copolymerize vinyl chloride monomer, vinyl acetate monomer and vinyl alcohol in an appropriate ratio. The other is to copolymerize vinyl chloride and vinyl acetate and then partially saponify the vinyl acetate. The vinyl chloride-vinyl acetate copolymer resin having hydroxyl groups determines the properties of the resin film and the resin dissolution behavior according to the monomer ratio of vinyl chloride, vinyl acetate and vinyl alcohol. That is, vinyl chloride gives toughness and hardness to the resin film, vinyl acetate gives adhesion and flexibility, and vinyl alcohol gives good solubility in polar solvents.
[0087] Regarding the monomer ratio of vinyl chloride-vinyl acetate copolymer resin, in order to meet the properties such as adhesion, anti-blocking, lamination strength, boiling and steaming adaptability, and printing adaptability, vinyl chloride is preferably 80 to 95 parts by mass relative to 100 parts by mass of vinyl chloride-vinyl acetate copolymer resin. If it is more than 80 parts by mass, the toughness of the resin film can be maintained and anti-blocking properties can be ensured. If it is less than 95 parts by mass, the resin film will not become too hard and the adhesion is not easy to decrease. In addition, the hydroxyl value obtained from vinyl alcohol is preferably 50 to 200 mgKOH / g. If it is more than 50 mgKOH / g, the solubility in polar solvents is good and the printing adaptability is also easy to stabilize. If it is less than 200 mgKOH / g, the water resistance will not decrease, and the boiling and steaming adaptability are also kept good.
[0088] The butyral resin is not particularly limited, and a known butyral resin can be used. Preferably, a polyvinyl butyral resin obtained by acetalizing butyraldehyde with polyvinyl alcohol by a known reaction is used.
[0089] The weight average molecular weight of the polyvinyl butyral resin is preferably 5,000 to 60,000, more preferably 6,000 to 50,000, and even more preferably 7,000 to 40,000.
[0090] The hydroxyl group content of the polyvinyl butyral resin is preferably in the range of 10 to 30% by mass, more preferably 15 to 25% by mass. The acetyl group content of the polyvinyl butyral resin (B) is preferably 10% by mass or less.
[0091] The content ratio of these other resins having a glass transition temperature of 40°C or higher relative to the polyester resin (A) is preferably polyester resin (A): other resins having a glass transition temperature of 40°C or higher = 10:90 to 90:10, more preferably 40:60 to 80:20 in terms of solid content ratio.
[0092] (Colorant)
[0093] As the colorant used in the present invention, organic and inorganic pigments and dyes used in general inks, coatings and recording agents can be cited. As organic pigments, azo, phthalocyanine, anthraquinone, perylene, perinone, quinacridone, thioindigo, dioxazine, isoindolinone, quinophthalone, azomethine, diketopyrrolopyrrole, isoindolinone and the like pigments can be cited. Copper phthalocyanine is preferably used for blue ink, and CI pigment No Yellow 83 is preferably used for transparent yellow ink from the viewpoint of cost and light resistance.
[0094] As inorganic pigments, carbon black, titanium oxide, zinc oxide, zinc sulfide, barium sulfate, calcium carbonate, chromium oxide, silicon dioxide, red iron oxide, aluminum, mica, kaolin, etc. can be cited. In addition, a bright pigment (METASHINE; Nippon Sheet Glass Co., Ltd.) coated with a metal or metal oxide on the basis of a glass flake or a block flake as a base material can be used. From the viewpoint of cost and coloring power, it is preferred that titanium oxide be used for white ink, carbon black be used for black ink, aluminum be used for gold and silver inks, and mica be used for pearlescent ink. Aluminum is in the form of powder or paste. From the perspective of operability and safety, it is preferably used in the form of a paste. From the perspective of brightness and concentration, a floating type or a non-floating type is appropriately selected and used.
[0095] The colorant is preferably contained in an amount sufficient to ensure the concentration and coloring power of the ink, that is, in a ratio of 1 to 60% by weight relative to the total weight of the ink. The colorant may be used alone or in combination of two or more.
[0096] (Organic Solvent)
[0097] Next, the organic solvent used in the present invention is described. In the liquid ink composition of the present invention, for example, there can be mentioned aromatic organic solvents, acetone, methyl ethyl ketone, methyl isobutyl ketone and other ketone solvents; ester solvents such as ethyl acetate, n-propyl acetate, butyl acetate, propylene glycol monomethyl ether acetate and the like; alcohol solvents such as ethanol, n-propanol, isopropanol, n-butanol, propylene glycol monomethyl ether, glycol ester solvents, which can be used alone or as a mixture of two or more. From the perspective of cost, toluene can also be used as the main component, but in recent years, from the perspective of the working environment, it is preferred not to use aromatic solvents such as toluene and xylene and ketone solvents. Furthermore, the liquid ink of the present invention can also be designed as a single ester solvent. Ester-based single solvents are suitable as single-solvent inks that can be solvent-recovered as required in recent years.
[0098] (additive)
[0099] In the present invention, resin, extender pigment, pigment dispersant, leveling agent, defoaming agent, wax, plasticizer, infrared absorber, ultraviolet absorber, fragrance, flame retardant and the like may be contained in combination as necessary.
[0100] Regarding the liquid ink composition of the present invention, in order to improve the anti-blocking property, wax, silica, and extender pigment as an anti-blocking agent may be dissolved and / or dispersed in the ink and added. These may be used alone or in combination of two or more.
[0101] Various known waxes can be used as the wax. Examples of the wax include polyolefin waxes and amide waxes, among which amide waxes are preferred due to their excellent dispersibility. As the amide wax, fatty acid amide wax is preferred. As the fatty acid amide, palmitic acid amide, stearic acid amide, ethylene bisoleic acid amide, hexamethylene bisoleic acid amide, erucic acid amide, etc. can be cited, among which palmitic acid amide, stearic acid amide, ethylene bisoleic acid amide, hexamethylene bisoleic acid amide are more preferred.
[0102] Examples of silica include silica compounds such as silicon dioxide, epoxy-modified silicone, amino-modified silicone, and polyester-modified silicone. Among them, granular silicon dioxide having an average particle size of 1 to 20 μm is preferred, and 2 to 10 μm is more preferred.
[0103] Among them, from the viewpoint of dispersibility, stability and anti-blocking effects, amide wax and silica are preferably used, and their combined use is more preferred.
[0104] From the viewpoint of lamination suitability, the total amount of these anti-blocking agents contained in the ink is preferably 5% by weight or less, and more preferably in the range of 0.1 to 3.0% by weight.
[0105] In order to disperse the pigment stably in the organic solvent, the above-mentioned resin can be dispersed alone, but in order to further stably disperse the pigment, a dispersant can also be used in combination. As a dispersant, anionic, nonionic, cationic, zwitterionic and other surfactants can be used. For example, a comb-shaped structure polymer compound formed by adding polyester to polyethyleneimine, or an alkylamine derivative of an α-olefin maleic acid polymer can be cited. Specifically, BYK series (BYK Chemical), EFKA series (EFKA), Solsperse series (Lubrizol), Ajisper series (Ajinomoto), Homogenol series (Kao), etc. can be cited. Regarding the dispersant, it is preferred that in the ink, from the viewpoint of the storage stability of the ink, it contains 0.05% by weight or more relative to the total weight of the ink, and from the viewpoint of lamination adaptability, it contains 5% by weight or less, and more preferably in the range of 0.1 to 2% by weight.
[0106] The liquid ink composition of the present invention may be used in either a one-component type in which no curing agent such as an isocyanate curing agent is used or a two-component type in which a curing agent is used.
[0107] The liquid ink composition of the present invention can be produced by dissolving and / or dispersing a resin, a colorant, etc. in an organic solvent. Specifically, the ink can be produced by preparing a pigment dispersion in which a pigment is dispersed in an organic solvent using a polyester resin, and optionally adding other compounds to the obtained pigment dispersion.
[0108] The particle size distribution of the pigment in the pigment dispersion can be adjusted by appropriately adjusting the size of the pulverizing media of the disperser, the filling rate of the pulverizing media, the dispersion treatment time, the discharge speed of the pigment dispersion, the viscosity of the pigment dispersion, etc. As the disperser, commonly used ones such as a roll mill, a ball mill, a pebble mill, an attritor, a sand mill, etc. can be used.
[0109] When air bubbles, unexpected large particles, and the like are contained in the ink, the quality of the printed matter is degraded, and therefore, they are preferably removed by filtration or the like. As the filter, a conventionally known filter can be used.
[0110] The viscosity of the ink produced by the above method is preferably 10 mPa·s or more from the viewpoint of preventing the sedimentation of the pigment and properly dispersing it, and preferably 2000 mPa·s or less from the viewpoint of workability efficiency during ink production and printing. It should be noted that the above viscosity is the viscosity measured at 25° C. using a B-type viscometer manufactured by Tokimec.
[0111] The viscosity of the liquid ink composition of the present invention is preferably in the range of 10 to 24, and more preferably in the range of 15 to 20, as measured at 25° C. using Zahn cup #3 manufactured by Riki Corporation. This viscosity range is lower than that of conventional inks using a polyurethane resin system, and therefore the amount of solvent in the ink formulation during actual printing can be reduced, and an ink having an excellent balance among adhesion, lamination strength, anti-blocking properties, and printability can be obtained.
[0112] The viscosity of the ink can be adjusted by appropriately selecting the type and amount of the raw materials used, such as polyester resin, colorant, organic solvent, etc. In addition, the viscosity of the ink can also be adjusted by adjusting the particle size and particle size distribution of the pigment in the ink.
[0113] As the hue of the ink composition of the present invention, according to the type of colorant used, there are five colors of yellow, red, blue, black and white as the basic process colors, and three colors of red (orange), grass (green) and purple as the process color range colors. Furthermore, transparent yellow, peony, vermilion, brown, gold, silver, pearl, and a roughly transparent medium for adjusting the color concentration (including a body pigment as needed) are prepared as the base color. In the case of requiring boiling and steaming resistant inks and contents, the migration, heat resistance and alkali resistance of the pigment are considered and appropriately selected. The base ink of each hue is diluted with a diluting solvent to a viscosity and concentration suitable for gravure printing and flexographic inks, and supplied to each printing unit alone or mixed.
[0114] As the plastic film that can be used, polyester resin film, films obtained by treating the surface of polypropylene, polyethylene, polyamide, etc. with corona discharge are generally used. In consideration of the printing process and cost, untreated films are sometimes used. In addition, various high-function films coated with inorganic or organic barrier coating materials can also be widely used.
[0115] (Printed material)
[0116] The printed article of the present invention is a printed article comprising a substrate and a printing layer of the liquid ink composition of the present invention on the substrate. The liquid ink composition of the present invention has excellent adhesion to various substrates such as the above-mentioned plastic film. The substrate used is not particularly limited, and can be used for printing on resin films, paper, synthetic paper, plastic products, steel plates, etc. according to the desired application. For example, as a food packaging application, a film-like substrate can be used. Specifically, there can be mentioned films formed of the following thermoplastic resins, and their laminates. The thermoplastic resins are polyester resins such as polyethylene terephthalate (hereinafter sometimes referred to as PET), polyethylene naphthalate, polytrimethylene terephthalate, polytrimethylene naphthalate, polybutylene terephthalate, and polybutylene naphthalate, polyamides such as nylon 6, nylon 66, and nylon 46, polyhydroxycarboxylic acids such as polylactic acid, biodegradable resins such as aliphatic polyester resins such as poly(ethylene succinate) and poly(butylene succinate), polyolefins such as polypropylene (CPP: unstretched polypropylene film, OPP: biaxially stretched polypropylene film), polyethylene (LLDPE: low-density polyethylene film, HDPE: high-density polyethylene film), polyimide, polyarylate, polystyrene, polyacrylonitrile, polyvinyl alcohol, ethylene-vinyl alcohol copolymer, etc., or mixtures thereof. Among them, films composed of polyester, polyamide, polyethylene, and polypropylene can be preferably used.
[0117] In addition, it is also preferable to use a film formed of a material containing a biomass-derived component as the film substrate. Biomass films are sold by various companies, and for example, sheets listed in the list of biomass certified products recorded in the Japan Organic Resources Association can be used.
[0118] A specifically known membrane is a membrane using ethylene glycol derived from biomass as a raw material. Ethylene glycol derived from biomass is ethylene glycol made from ethanol (biomass ethanol) produced using biomass as a raw material. For example, for biomass ethanol, ethylene glycol derived from biomass can be obtained by a method known in the past, a method of generating ethylene glycol via ethylene oxide, etc. In addition, commercially available biomass ethylene glycol can also be used, for example, commercially available biomass ethylene glycol from India Glycol can be suitably used.
[0119] Alternatively, substances using biomass raw materials that are classified by the biomass plasticity specified in ISO16620 or ASTMD6866 are also circulated. Radioactive carbon 14C exists in the atmosphere at a ratio of 1 in 1012, and this ratio does not change in the carbon dioxide in the atmosphere, so this ratio does not change in plants that fix the carbon dioxide through photosynthesis. Therefore, the carbon of plant-derived resin contains radioactive carbon 14C. In contrast, the carbon of fossil fuel-derived resin contains almost no radioactive carbon 14C. Therefore, by measuring the concentration of radioactive carbon 14C in the resin with an accelerator mass spectrometer, the content ratio of plant-derived resin in the resin, that is, the biomass plasticity, can be calculated. As biomass plastics having a biomass plasticity of 80% or more, preferably 90% or more as specified in ISO16620 or ASTMD6866, i.e., low-density polyethylene of plant origin, for example, trade names such as "SBC818", "SPB608", "SBF0323 HC", "STN7006", "SEB853", "SPB681", etc. manufactured by Braskem can be cited, and films using them as raw materials can be appropriately used.
[0120] For example, as an alternative to conventional polyethylene terephthalate films made of petroleum raw materials, films containing biomass polyesters and biomass polyethylene terephthalate, etc., which contain biomass-derived ethylene glycol as diol units and fossil fuel-derived dicarboxylic acids as dicarboxylic acid units, are known.
[0121] The dicarboxylic acid unit of the biomass polyester uses a dicarboxylic acid derived from fossil fuels. As the dicarboxylic acid, aromatic dicarboxylic acids, aliphatic dicarboxylic acids, and derivatives thereof can be used without limitation.
[0122] In addition, it can also be a copolyester to which a copolymer component as a third component is added in addition to the above-mentioned diol component and dicarboxylic acid component, and the copolymer component as the third component is: a bifunctional hydroxycarboxylic acid, and at least one polyfunctional compound selected from the group consisting of a trifunctional or higher polyol, a trifunctional or higher polycarboxylic acid and / or its anhydride and a trifunctional or higher hydroxycarboxylic acid in order to form a cross-linked structure.
[0123] In addition, for example, as an alternative to conventional polyolefin membranes made of petroleum raw materials, biomass polyolefin membranes such as biomass polyethylene membranes and biomass polyethylene-polypropylene membranes containing polyethylene resins made of biomass-derived ethylene glycol as a raw material are also known.
[0124] Regarding polyethylene resins, there are no particular limitations except that the above-mentioned biomass-derived ethylene glycol is used as a part of the raw materials, and examples include homopolymers of ethylene, copolymers of ethylene and α-olefins with ethylene as the main component (ethylene-α-olefin copolymers containing 90% by mass or more of ethylene units), etc., and they can be used alone or in combination of two or more.
[0125] It should be noted that the α-olefin constituting the copolymer of ethylene and α-olefin is not particularly limited, and examples thereof include α-olefins having carbon atoms of 4 to 8, such as 1-butene, 4-methyl-1-pentene, 1-hexene, and 1-octene. Known polyethylene resins such as low-density polyethylene resins, medium-density polyethylene resins, and linear low-density polyethylene resins can be used.
[0126] Among them, from the viewpoint of being less likely to cause damage such as opening and cracking even when the films are rubbed against each other, linear low-density polyethylene resin (LLDPE) (copolymer of ethylene and 1-hexene or copolymer of ethylene and 1-octene) is preferred, and a density of 0.910 to 0.925 g / cm 3 Linear low-density polyethylene resin.
[0127] In addition, films and sheets containing starch and polylactic acid as biomass raw materials are also known, and these can be appropriately selected and used according to the application.
[0128] The biomembrane may be a laminated body formed by laminating a plurality of biomembranes, or may be a laminated body of a conventional petroleum-based membrane and a biomembrane.
[0129] These petroleum-based membranes and biomass membranes can be laminated with a vapor-deposited layer of metals such as aluminum, silicon dioxide, and metal oxides such as aluminum oxide, or use metal foil, or use a barrier film containing a gas barrier layer such as polyvinyl alcohol, ethylene-vinyl alcohol copolymer, and vinylidene chloride, or implement a coating treatment such as polyvinyl alcohol. By using such a film, a laminate having a higher barrier property against water vapor, oxygen, alcohol, inert gas, volatile organic matter (fragrance), etc. can be made.
[0130] In addition, these films can be unstretched films or films subjected to stretching treatment, and their preparation methods are also not limited. As a stretching treatment method, the resin is usually melt-extruded and made into a sheet by an extrusion film-making method, and then biaxial stretching or biaxial stretching is performed simultaneously. In addition, in the case of biaxial stretching, longitudinal stretching is usually performed first, followed by transverse stretching. Specifically, a method of combining longitudinal stretching using a speed difference between rollers with transverse stretching using a tenter is mostly used.
[0131] The thickness of the substrate film is not particularly limited and is usually in the range of 1 to 500 μm. The film surface may be subjected to various surface treatments such as flame treatment and corona discharge treatment as needed to form an adhesive layer without defects such as film breakage and dents.
[0132] There is no particular limitation on paper, and known paper substrates can be used. Specifically, natural fibers for papermaking such as wood pulp are used and are manufactured using known papermaking machines, but the papermaking conditions are not particularly specified. Natural fibers for papermaking include wood pulp such as conifer pulp and broadleaf pulp, non-wood pulp such as Manila hemp pulp, sisal pulp, and flax pulp, and pulp obtained by chemically modifying these pulps. As the type of pulp, chemical pulp, groundwood pulp, chemical groundwood pulp, thermomechanical pulp, etc. based on sulfate cooking, acid / neutral / alkaline sulfite cooking, sodium salt cooking, etc. can be used. In addition, various commercially available papers used in cosmetics, beverages, pharmaceuticals, toys, equipment, etc., such as high-quality paper, kraft paper, pure white roll paper, glassine paper, parchment paper, manila paperboard, white paperboard, coated paper, art paper, imitation paper, interlayer paper, impregnated paper, hardshell paper, cardboard, thin paper, thick paper, polyethylene coated paper, etc., can also be used.
[0133] As the printing method, known printing methods such as gravure printing and flexographic printing can be used, and gravure printing is particularly preferred. As the roller used in gravure printing, a known roller such as an engraved type or an etched type can be used.
[0134] The above-mentioned printing method, that is, after the printing ink is temporarily bonded and transferred to the printing plate or printing pattern, the ink is only bonded to the substrate again, and it is dried or cured in an oven as needed to fix it, thereby obtaining a printed matter. The film thickness of the printing ink formed by the gravure printing method or the flexographic printing method using the liquid printing ink of the present invention is, for example, 10 μm or less, preferably 5 μm or less.
[0135] The liquid printing ink of the present invention can be preferably used as a front printing ink, a back printing ink or a laminating ink. When used as a front printing ink, an overprint varnish layer can also be provided separately. On the other hand, when used as a back printing ink, an anchor coating varnish layer can also be provided separately.
[0136] In addition, the printed matter of the present invention may have not only one printed layer but also multiple printed layers on a substrate. For example, a laminate having at least a first printed layer and a second printed layer in sequence on a plastic film, or a laminate having at least a first printed layer, a second printed layer and a third printed layer in sequence on a plastic film may be produced. The liquid printing ink of the present invention may be used for these printed layers. More specifically, for example, a printed matter having a first printed layer formed by a printing ink containing a colorant, a second white printed layer formed by a liquid printing ink containing a white pigment as a colorant, and a third white printed layer in sequence may be produced. The first printed layer may form a pattern based on a colorant, and the second white printed layer and the third printed layer formed by a liquid printing ink containing a white pigment may be used as the background of the pattern. In the case where the second or third printed layer is set as an overprint varnish, a colorant may not be included.
[0137] (Laminated body)
[0138] The laminate of the present invention is obtained by laminating a plurality of substrates, and has a printed layer of the liquid ink composition of the present invention on at least one of the substrates. The substrates may be laminated by laminating with an adhesive or by extrusion lamination. The substrate may be the same as the substrate described in the above-mentioned printed matter.
[0139] As a more specific structure of the laminated body, the following can be mentioned:
[0140] (1) Base film 1 / Printing layer / Adhesive layer 1 / Sealing film
[0141] (2) Base film 1 / Printing layer / Adhesive layer 1 / Metal-deposited unstretched film
[0142] (3) Base film 1 / Printing layer / Adhesive layer 1 / Metal-deposited stretched film
[0143] (4) Transparent vapor-deposited stretch film / printing layer / adhesive layer 1 / sealing film
[0144] (5) Base film 1 / printing layer / adhesive layer 1 / base film 2 / adhesive layer 2 / sealing film
[0145] (6) Base film 1 / Printing layer / Adhesive layer 1 / Metal-deposited stretched film / Adhesive layer 2 / Sealing film
[0146] (7) Base film 1 / Printing layer / Adhesive layer 1 / Transparent vapor-deposited stretched film / Adhesive layer 2 / Sealing film
[0147] (8) Base film 1 / Printing layer / Adhesive layer 1 / Metal layer / Adhesive layer 2 / Sealing film
[0148] (9) Base film 1 / printing layer / adhesive layer 1 / base film 2 / adhesive layer 2 / metal layer / adhesive layer 3 / sealing film
[0149] (10) Base film 1 / printing layer / adhesive layer 1 / metal layer / adhesive layer 2 / base film 2 / adhesive layer 3 / sealing film
[0150] etc., but is not limited thereto. It should be noted that the "printing layer" herein refers to the printing layer of the liquid ink composition of the present invention. In addition, in the above-mentioned configurations (1) to (10), the printing layer is provided on the surface of the substrate film 1 on the side of the adhesive layer 1, but the printing layer may also be provided on the surface (surface) of the substrate film 1 opposite to the adhesive layer 1, or the printing layer may be provided on the substrate film 2.
[0151] As the substrate film 1 used in the constitution (1), OPP film, PET film, nylon film (hereinafter also referred to as Ny film) and the like can be cited. In addition, as the substrate film 1, a substrate film coated for the purpose of improving gas barrier properties and ink absorption when a printing layer is provided as described later can also be used. As commercially available products of the substrate film 1 coated, K-OPP film, K-PET film and the like can be cited. As the sealing film, CPP film, LLDPE film and the like can be cited.
[0152] As the base film 1 used in the constitutions (2) and (3), OPP film, PET film, etc. can be cited. As the metal-deposited unstretched film, VM-CPP film obtained by vapor-depositing a metal such as aluminum on a CPP film can be used, and as the metal-deposited stretched film, VM-OPP film obtained by vapor-depositing an metal such as aluminum on an OPP film can be used.
[0153] As the transparent vapor-deposited stretched film used in the constitution (4), there can be mentioned films obtained by vapor-depositing silica or alumina on OPP films, PET films, nylon films, etc. In order to protect the inorganic vapor-deposited layer of silica or alumina, a film coated on the vapor-deposited layer can be used. The sealing film can be the same as the sealing film in the constitution (1).
[0154] Examples of the base film 1 used in the configuration (5) include PET films, etc. Examples of the base film 2 include nylon films, etc. Examples of the sealing film include the same sealing films as those in the configuration (1).
[0155] As the base film 1 of the constitution (6), the same base film as in the constitutions (2) and (3) can be cited. As the metallized stretched film, VM-OPP film and VM-PET film in which a metal such as aluminum is deposited on an OPP film or a PET film can be cited. As the sealing film, the same sealing film as in the constitution (1) can be cited.
[0156] Examples of the base film 1 of the configuration (7) include PET films, etc. Examples of the transparent vapor-deposited stretched film include the same transparent vapor-deposited stretched film as in the configuration (4), and examples of the sealing film include the same sealing film as in the configuration (1).
[0157] Examples of the base film 1 of the configuration (8) include PET films, etc. Examples of the metal layer include aluminum foils, etc. Examples of the sealing film include the same sealing films as those of the configuration (1).
[0158] Examples of the base film 1 in the configurations (9) and (10) include PET films, etc. Examples of the base film 2 include nylon films, etc. Examples of the metal layer include aluminum foils, etc. Examples of the sealing film include the same sealing films as those in the configuration (1).
[0159] (Adhesive layer)
[0160] The adhesive layer may be appropriately made of a known adhesive for film lamination. In addition, when laminating by extrusion lamination, an anchor coating agent for extrusion lamination may be appropriately used as an adhesive aid. If a material having gas barrier properties is used as these adhesives and anchor coating agents, a laminate having particularly excellent barrier properties can be obtained.
[0161] As an adhesive with excellent gas barrier properties, it is particularly preferred to satisfy the requirement of 3 g / m 2 (Solid content) The oxygen barrier property of the cured coating film of the applied adhesive is 300 cc / m 2 / day / atm or less, or water vapor barrier of 120g / m 2 As commercial products, there are "PASLIM" series such as PASLIM VM001 and PASLIM J350 X manufactured by DIC Corporation, and "MAXIVE" manufactured by Mitsubishi Gas Chemical Co., Ltd.
[0162] The adhesive layer is not particularly limited, and known materials can be used, preferably a cured product containing polyols and isocyanate compounds. When these polyols and / or isocyanate compounds use materials containing biomass-derived components, a laminate with a high biomass content can be made, which can reduce environmental load.
[0163] From the viewpoint of gas barrier properties and adhesion, the cured product of a polyol and an isocyanate compound can preferably use a two-component adhesive composed of a polyol composition (A) and a polyisocyanate composition (B), wherein the polyol composition (A) contains at least one polyester polyol selected from the group consisting of (A1) to (A5) below, and the polyisocyanate composition (B) contains a compound having at least two isocyanate groups in one molecule (hereinafter also referred to as an isocyanate compound).
[0164] (1) Polyester polyol (A1) obtained by reacting a carboxylic acid anhydride or a polycarboxylic acid with a polyester polyol having three or more hydroxyl groups
[0165] (2) Polyester polyol having polymerizable carbon-carbon double bonds (A2)
[0166] (3) Polyester polyol having a glycerol skeleton (A3)
[0167] (4) Polyester polyol (A4) obtained by polycondensing ortho-aligned polycarboxylic acid and polyol
[0168] (5) Polyester polyol having an isocyanurate ring (A5)
[0169] The hydroxyl value of the polyester polyol is preferably 20 mgKOH / g or more and 250 mgKOH / g or less. In addition, when the polyester polyol has an acid group, the acid value is preferably 200 mgKOH / g or less. In addition, the lower limit of the acid value of the polyester polyol is not particularly limited, and as an example, it is 20 mgKOH / g or more. The hydroxyl value of the polyester polyol can be measured by the hydroxyl value determination method described in JIS-K0070, and the acid value can be measured by the acid value determination method described in JIS-K0070.
[0170] If the number average molecular weight of the polyester polyol is 300 to 5000, a crosslinking density that is excellent in the balance between adhesion and gas barrier properties can be obtained, which is particularly preferred. The more preferred number average molecular weight is 350 to 3000. The number average molecular weight is calculated from the obtained hydroxyl value and the number of functional groups of the designed hydroxyl group. In addition, the glass transition temperature of the polyester polyol is preferably above -30°C and below 80°C, more preferably above 0°C and below 60°C, and further preferably above 25°C and below 60°C.
[0171] The polyester polyol may be a polyester polyurethane polyol obtained by urethane-extending polyester polyols (A1) to (A5) by reacting with a diisocyanate compound to give a number average molecular weight of 1000 to 15000. Urethane-extended polyester polyols have a molecular weight component of a certain level or more and urethane bonds, and therefore have excellent gas barrier properties, excellent initial cohesive strength, and are excellent as adhesives for lamination.
[0172] The polyisocyanate composition (B) as a component of the two-component adhesive having gas barrier properties contains an isocyanate compound. As the isocyanate compound, conventionally known isocyanate compounds can be used without particular limitation, and examples thereof include the following isocyanates or dimers and trimers of these isocyanate compounds, and adducts obtained by reacting excess amounts of these isocyanate compounds with the following low molecular weight active hydrogen compounds and alkylene oxide adducts thereof, various polyester resins, polyether polyols, and high molecular weight active hydrogen compounds of polyamides, wherein the isocyanates are tetramethylene diisocyanate, hexamethylene diisocyanate, Acid, toluene diisocyanate, diphenylmethane diisocyanate, hydrogenated diphenylmethane diisocyanate, xylylene diisocyanate, hydrogenated xylylene diisocyanate, isophorone diisocyanate, and the low molecular active hydrogen compound is, for example, ethylene glycol, propylene glycol, m-xylylene glycol, 1,3-bishydroxyethylbenzene, 1,4-bishydroxyethylbenzene, trimethylolpropane, glycerol, pentaerythritol, erythritol, sorbitol, ethylenediamine, monoethanolamine, diethanolamine, triethanolamine, m-xylylenediamine, etc. A polyester polyisocyanate obtained by reacting polyester polyols (A1) to (A5) with a diisocyanate compound in a manner that the ratio of hydroxyl group to isocyanate group is an excess of isocyanate can also be used. These can be used alone or in combination of two or more.
[0173] In addition, blocked isocyanates can also be used as isocyanate compounds. Examples of isocyanate blocking agents include phenols such as phenol, thiophenol, methylthiophenol, ethylthiophenol, cresol, xylenol, resorcinol, nitrophenol, and chlorophenol; oximes such as acetone oxime, methyl ethyl ketone oxime, and cyclohexanone oxime; alcohols such as methanol, ethanol, propanol, and butanol; halogen-substituted alcohols such as chloroethanol and 1,3-dichloro-2-propanol; tertiary alcohols such as tert-butyl alcohol and tert-amyl alcohol; lactams such as ε-caprolactam, δ-valerolactam, γ-butyrolactam, and β-propiolactam; and active methylene compounds such as aromatic amines, imides, acetylacetone, acetoacetate, and ethyl malonate, thiols, imines, ureas, and diaryl compounds such as sodium bisulfite. The blocked isocyanate can be obtained by subjecting the above-mentioned isocyanate compound to an addition reaction with an isocyanate blocking agent by a known and commonly used appropriate method.
[0174] Among them, from the viewpoint of obtaining good gas barrier properties, xylylene diisocyanate, hydrogenated xylylene diisocyanate, toluene diisocyanate, and diphenylmethane diisocyanate are preferred, and isocyanate compounds having a meta-xylene skeleton such as meta-xylylene diisocyanate and hydrogenated meta-xylylene diisocyanate are more preferred.
[0175] In addition, when a composition containing a polyester polyol having a residual carboxylic acid group such as polyester polyol (A1) is used as the polyol composition (A), the polyisocyanate composition (B) may contain a known epoxy compound. In addition, when a composition containing a polyol having a polymerizable carbon-carbon double bond such as polyester polyol (A2) is used, in order to promote the polymerization of the carbon-carbon double bond, a known polymerization catalyst may be used in combination, for example, a known transition metal complex or a photopolymerization initiator may be used in combination.
[0176] The polyol composition (A) and the polyisocyanate composition (B) are preferably mixed in such a manner that the equivalent ratio of the hydroxyl group contained in the polyol composition (A) to the isocyanate group contained in the polyisocyanate composition (B) is 1 / 0.5 to 1 / 10, and more preferably in such a manner that it is 1 / 1 to 1 / 5. In the case of an excess of isocyanate compound, the remaining isocyanate compound remaining in the cured coating film of the adhesive may ooze out from the adhesive layer. On the other hand, when the reactive functional group contained in the polyisocyanate composition (B) is insufficient, the bonding strength may be insufficient.
[0177] In the gas barrier adhesive, various additives can be added within the range that does not impair the adhesiveness and gas barrier properties. For example, an inorganic filler can be used. As the inorganic filler, silicon dioxide, aluminum oxide, aluminum flakes, glass flakes, etc. can be mentioned. In particular, when a plate-like inorganic compound is used as the inorganic filler, the adhesive strength, gas barrier properties, light shielding properties, etc. are improved, so it is preferred. Examples of the plate-like inorganic compound include hydrous silicates (layered silicate minerals, etc.), kaolinite-serpentine group clay minerals (halloysite, kaolinite, endellite, dickite, nacrite, etc., antigorite, chrysotile, etc.), pyrophyllite-talc group (pyrophyllite, talc, kerolite, etc.), montmorillonite group clay minerals (montmorillonite, beidellite, nontronite, saponite, hectorite, sauconite, stevensite, etc.), vermiculite group clay minerals (vermiculite, etc.), mica or mica group clay minerals (muscovite, phlogopite and other micas, nacrite, tetrasilicon mica, taenia mica, etc.), chlorite group (lithophore, sudosite, clinochlore, oolite, nickel chlorite, etc.), hydrotalcite, plate-like barium sulfate, boehmite, aluminum polyphosphate, etc. These minerals may be natural clay minerals or synthetic clay minerals. The plate-like inorganic compound may be used alone or in combination of two or more.
[0178] In addition, it may contain adhesion promoters, acid anhydrides, compounds having an oxygen scavenging function, tackifiers, gas barrier adhesives, stabilizers (antioxidants, heat stabilizers, ultraviolet absorbers, etc.), plasticizers, antistatic agents, lubricants, antiblocking agents, colorants, crystal nucleating agents, etc. These various additives may be added in advance to either or both of the polyol composition (A) and the polyisocyanate composition (B), or may be added when the polyol composition (A) and the polyisocyanate composition (B) are mixed.
[0179] In addition, the gas barrier adhesive used may be any of a solvent type and a solvent-free type. When the gas barrier adhesive used is a solvent type, the adhesive of the present invention is applied to the printed layer printed on the first substrate using a roller such as a gravure roller, and after the organic solvent is volatilized by heating in an oven, another substrate is attached to obtain the laminate of the present invention. It is preferred to perform an aging treatment after lamination. The aging temperature is preferably room temperature to 80°C, and the aging time is preferably 12 to 240 hours.
[0180] When the gas barrier adhesive used is a solvent-free type, the adhesive of the present invention preheated to about 40°C to 100°C is applied to the printed layer printed on the first substrate using a roller such as a gravure roller, and then another substrate is immediately bonded to obtain the laminate of the present invention. It is preferred to perform an aging treatment after lamination. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0181] When the gas barrier adhesive is used as an adhesive aid, the adhesive aid of the present invention is applied to the printed layer printed on the first substrate using a roller such as a gravure roller, and the organic solvent is volatilized by heating in an oven, etc., and then the molten polymer material is laminated using an extruder to obtain the laminate of the present invention. As the molten polymer material, a polyolefin resin such as a low-density polyethylene resin, a linear low-density polyethylene resin, and an ethylene-vinyl acetate copolymer resin is preferred. The aging temperature is preferably room temperature to 70°C, and the aging time is preferably 6 to 240 hours.
[0182] The amount of gas barrier adhesive to be applied is appropriately adjusted. In the case of a solvent-based adhesive, for example, a solid content of 1 g / m 2 Above and 10g / m 2 Below, preferably 2g / m 2 Above and 5g / m 2 In the case of a solvent-free adhesive, as an example, the amount of adhesive applied is 1 g / m 2 Above and 5g / m 2 Below, preferably 1g / m 2 Above and 3g / m 2 the following.
[0183] When using an adhesive as an adhesive aid, the coating amount is appropriately adjusted, and as an example, it is 0.03 g / m 2 Above and 2g / m 2 Below (solid content).
[0184] (Other layers of laminate)
[0185] The laminate of the present invention can be used alone or further include other films and substrates. As other substrates, in addition to the above-mentioned stretched film, unstretched film, and transparent vapor-deposited film, porous substrates such as paper, wood, and leather can also be used. The adhesive used when laminating other substrates can use the gas barrier adhesive as described above, or it can not be used.
[0186] <Packaging Materials>
[0187] The printed matter and laminate of the present invention can be used as a multilayer packaging material for the purpose of protecting food, medicines, etc. When used as a multilayer packaging material, the layer structure can be changed according to the content, use environment, and use form.
[0188] The packaging material of the present invention is obtained by, for example, using the laminate of the present invention, overlapping the surfaces of the sealing films of the laminate relative to each other, and then heat-sealing the peripheral ends thereof. As a bag-making method, the following method can be cited: the laminate of the present invention is bent or overlapped so that the surfaces of its inner layers (surfaces of the sealing films) are relative to each other, and the peripheral ends thereof are heat-sealed by, for example, side sealing type, double-sided sealing type, three-sided sealing type, four-sided sealing type, envelope pasting sealing type, palm-to-palm pasting sealing type, pleated sealing type, flat bottom sealing type, square bottom sealing type, gusseted type, other heat-sealing types, and the like. The packaging material of the present invention can take various forms according to the contents, use environment, and use form. It can also be a self-supporting packaging material (self-supporting bag), etc. As a heat-sealing method, it can be carried out by known methods such as rod sealing, rotary roller sealing, belt sealing, impulse sealing, high-frequency sealing, and ultrasonic sealing.
[0189] In the packaging material of the present invention, after the contents are filled from the opening, the opening is heat-sealed to produce a product using the packaging material of the present invention.
[0190] Example
[0191] The present invention is described in more detail below with reference to Examples. Hereinafter, "parts" and "%" are based on weight.
[0192] In addition, the measurement of the weight average molecular weight (polystyrene conversion) by GPC (gel permeation chromatography) in the present invention was performed under the following conditions using HLC8220 system manufactured by Tosoh Corporation.
[0193] Separation columns: 4 TSKgelGMH manufactured by Tosoh Corporation HR -N. Column temperature: 40°C. Mobile layer: Tetrahydrofuran manufactured by Wako Pure Chemical Industries, Ltd. Flow rate: 1.0 ml / min. Sample concentration: 1.0 wt%. Sample injection volume: 100 μl. Detector: Differential refractometer.
[0194] The viscosity was measured at 25°C using a B-type viscometer manufactured by Tokimec Corporation.
[0195] (Synthesis example 1)
[0196] 619.3 parts by mass of neopentyl glycol, 504.8 parts by mass of adipic acid, and 0.07 parts by mass of tetraisopropyl titanate as a catalyst were added to a reaction vessel equipped with a stirrer, a condenser, and a thermometer. The mixture was reacted at 200 to 220° C. for 20 hours while being stirred under a nitrogen stream to obtain a polyester resin A having a number average molecular weight (Mn) of 400 and a hydroxyl value of 280 mgKOH / g.
[0197] (Synthesis example 2)
[0198] 538.2 parts by mass of neopentyl glycol, 612.4 parts by mass of adipic acid, and 0.07 parts by mass of tetraisopropyl titanate as a catalyst were placed in a reaction vessel equipped with a stirrer, a condenser, and a thermometer. The mixture was reacted at 200 to 220° C. for 20 hours while being stirred under a nitrogen stream to obtain a polyester resin B having a number average molecular weight (Mn) of 1,000 and a hydroxyl value of 110 mgKOH / g.
[0199] (Synthesis example 3)
[0200] 500.0 parts by mass of neopentyl glycol, 663.1 parts by mass of adipic acid, and 0.07 parts by mass of tetraisopropyl titanate as a catalyst were placed in a reaction vessel equipped with a stirrer, a condenser, and a thermometer. The mixture was reacted at 200 to 220° C. for 20 hours while being stirred under a nitrogen stream to obtain a polyester resin C having a number average molecular weight (Mn) of 3,200 and a hydroxyl value of 30 mgKOH / g.
[0201] (Synthesis Example 4)
[0202] 495.2 parts by mass of neopentyl glycol, 669.4 parts by mass of adipic acid, and 0.07 parts by mass of tetraisopropyl titanate as a catalyst were placed in a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and reacted at 200 to 220° C. for 20 hours while stirring under a nitrogen stream to obtain a polyester resin D having a number average molecular weight (Mn) of 5,000 and a hydroxyl value of 20 mgKOH / g.
[0203] (Synthesis Example 5)
[0204] 490.5 parts by mass of neopentyl glycol, 675.8 parts by mass of adipic acid, and 0.07 parts by mass of tetraisopropyl titanate as a catalyst were placed in a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and reacted at 200 to 220° C. for 20 hours while stirring under a nitrogen stream to obtain a polyester resin E having a number average molecular weight (Mn) of 20,000 and a hydroxyl value of 10 mgKOH / g.
[0205] (Synthesis Example 6)
[0206] 489.5 parts by mass of neopentyl glycol, 677.0 parts by mass of adipic acid, and 0.07 parts by mass of tetraisopropyl titanate as a catalyst were placed in a reaction vessel equipped with a stirrer, a condenser, and a thermometer, and reacted at 200 to 220° C. for 20 hours while stirring under a nitrogen stream to obtain a polyester resin F having a number average molecular weight (Mn) of 21,000 and a hydroxyl value of 8 mgKOH / g.
[0207] (Chlorinated polyolefin PP1)
[0208] As chlorinated polypropylene PP1, Superchlon 360T (manufactured by Nippon Paper Industries, Ltd.) (chlorination degree: 32%, weight average molecular weight: 12,000) was used.
[0209] (Chlorinated polyolefin PP2)
[0210] As chlorinated polypropylene PP2, Superchlon 814H (manufactured by Nippon Paper Industries, Ltd.) (chlorination degree 41%, weight average molecular weight 21,000) was used.
[0211] (Chlorinated polyolefin PP3)
[0212] As chlorinated polypropylene PP3, Superchlon 803M (manufactured by Nippon Paper Industries, Ltd.) (chlorination degree 30%, weight average molecular weight 110,000) was used.
[0213] (Nitrocellulose resin N)
[0214] Industrial nitrocellulose L1 / 8 (nitrocellulose, solid content 30%, product according to JIS K-6703, viscosity 1.6 to 2.9% at solution concentration 25.0%, manufactured by Taihei Chemical Products Co., Ltd.) was used.
[0215] (Acrylic resin Ac)
[0216] As the acrylic resin, DIANAL BR-90 (manufactured by Mitsubishi Chemical Corporation) was used.
[0217] (Vinyl chloride vinyl acetate copolymer resin B-1)
[0218] A vinyl chloride-vinyl acetate copolymer resin having a hydroxyl group was used (the resin monomer composition was vinyl chloride / vinyl acetate / vinyl alcohol = 92 / 3 / 5 in weight %, and the hydroxyl value (mg KOH) = 64).
[0219] (Vinyl chloride vinyl acetate copolymer resin B-2)
[0220] A vinyl chloride-vinyl acetate copolymer resin (the resin monomer composition in terms of weight %) was used: vinyl chloride / vinyl acetate=87 / 13.
[0221] (Polyvinyl butyral resin)
[0222] As the polyvinyl butyral resin, Mowital B 16H (manufactured by Kuraray) was used.
[0223] (Ketone resin)
[0224] As the ketone resin, Tego Variplus AP (manufactured by EVONIC) was used.
[0225] (Preparation of Cellulose Acetate Propionate CAP Resin Solution)
[0226] Cellulose acetate propionate CAP482-0.5 (manufactured by Eastman Chemical Co.) was used.
[0227] (Preparation of Cellulose Acetate Butyrate CAB Resin Solution)
[0228] Cellulose acetate butyrate CAB381-0.5 (manufactured by Eastman Chemical Company) was used.
[0229] (Preparation of polyurethane resin solution U)
[0230] In a four-necked flask equipped with a stirrer, a thermometer, a reflux condenser and a nitrogen inlet tube, 80 parts of neopentyl glycol adipate diol (hydroxyl value: 56.6 mgKOH / g), 20 parts of polyethylene glycol (hydroxyl value: 278 mgKOH / g) and 29.68 parts of isophorone diisocyanate were added, and reacted at 90°C for 10 hours under a nitrogen stream to produce a urethane prepolymer having an isocyanate group content of 2.84% by weight, and 69.8 parts of ethyl acetate were added thereto to prepare a uniform solution of the urethane prepolymer. Next, the urethane prepolymer solution was added to a mixture containing 7.97 parts of isophorone diamine, 0.11 parts of di-n-butylamine, 139.1 parts of ethyl acetate and 112.5 parts of isopropyl alcohol, and the mixture was stirred and reacted at 45°C for 5 hours to obtain a polyurethane resin solution U. The obtained polyurethane resin solution U had a resin solid content concentration of 30.4% by weight, a urea bond concentration = {(29.68÷222×2-(80×56.6+20×278)÷56100)×1000 / 137.76=0.64 mmol / g, and a weight average molecular weight (hereinafter referred to as Mw) of the resin solid content was 54,000.
[0231] [Example 1]
[0232] A mixture of 10 parts of the obtained polyester resin, 0.3 parts of a chlorinated polyolefin resin, 10 parts of a phthalocyanine blue pigment (FASTGEN Blue LA5380 manufactured by DIC Corporation), 1.0 part of an amide wax (CRODAMIDE SR Powder manufactured by CRODA Corporation), 0.5 parts of silica (Syloid ED2 manufactured by Grace Corporation), and 78.5 parts of ethyl acetate was kneaded to prepare a blue printing ink.
[0233] The viscosity of the obtained printing ink was measured using Zahn cup #3 (manufactured by Lihe Co., Ltd.), and the ink was printed on the OPP film (manufactured by Futamura Chemical Co., Ltd., trade name FOR, thickness 20 μm), PET film (manufactured by Toyobo Seisaku-shi Co., Ltd., trade name Ester E5102, thickness 12 μm), and nylon film (manufactured by Unitika Co., Ltd., trade name Embion ON, thickness 15 μm) shown in Table 1, respectively, and dried at 40°C to 50°C to obtain printed materials.
[0234] The obtained printed materials were evaluated for adhesion to various films, polyethylene extrusion lamination strength, dry lamination strength, anti-blocking, high light transfer, fogging properties, and viscosity stability. The results are shown in Table 1. It should be noted that the evaluation was performed by the following test method.
[0235] 1) Adhesion
[0236] After the printed matter was left to stand for 1 day, a transparent tape (manufactured by NICHIBAN, 12 mm wide) was attached to the printed surface, and the appearance of the printed film was visually determined when the tape was quickly peeled off. The determination criteria were as follows.
[0237] 5: The printed film is not peeled off at all. (Best)
[0238] 4: More than 80% of the printed film remains on the film.
[0239] 3: 40 to 80% of the printed film remains on the film.
[0240] 2: 10 to 40% of the printed film remains on the film.
[0241] 1: Less than 10% of the printed film remains on the film. (Worst)
[0242] 2) Determination of polyethylene extrusion lamination strength
[0243] The polyethyleneimine-based anchoring agent DIC DRYAC-108 (manufactured by DIC) was coated on the above-mentioned printed material (printed material using PET film), and polyethylene was laminated using a polyethylene extrusion laminator (manufactured by Sumitomo Heavy Industries, Ltd.). After 24 hours, a 15 mm width was cut out and a 90 degree peel test (measurement of lamination strength before boiling treatment) was carried out at a tensile speed of 300 mm / min.
[0244] 5: 200N / 15mm or more. (Best)
[0245] 4: 150~200N / 15mm.
[0246] 3: 100~150N / 15mm.
[0247] 2: 50~100N / 15mm.
[0248] 1: Less than 50N / 15mm. (Worst)
[0249] 3) Determination of dry lamination (solvent-based adhesive lamination) strength
[0250] An unstretched polypropylene film (hereinafter referred to as CPP: PYLEN Film-CT P1128, 30 μm, manufactured by Toyobo Co., Ltd.) was laminated on the above-mentioned printed material (printed material using PET film) using an ether-based dry laminating adhesive DIC DRYLX-401A / SP-60 (manufactured by DIC) using a dry laminator (manufactured by DIC Engineering). The laminate was aged at 40°C for 3 days, and then cut into pieces with a width of 15 mm. A 90-degree peel test (measurement of lamination strength before steaming treatment) was performed at a tensile speed of 300 mm / min.
[0251] 5: 300N / 15mm or more. (Best)
[0252] 4: 200~300N / 15mm.
[0253] 3: 150~200N / 15mm.
[0254] 2: 50~150N / 15mm.
[0255] 1: Less than 50N / 15mm. (Worst)
[0256] 4) Anti-adhesion
[0257] The printed material (the printed material using the PET film) was laminated so that the printed surface and the non-printed surface were in contact with each other, and a 10 kgf / cm 2 The test pieces were placed under a load of 100° C. for 12 hours at 40° C., and after removal, the state of ink transfer to the non-printing surface was visually evaluated in three stages.
[0258] 5: The amount of ink transferred to the non-printing surface is 0% and no transfer is observed. (Best)
[0259] 4: Less than 20% transfer was observed.
[0260] 3: Less than 40% transfer was observed.
[0261] 2: Less than 60% transfer was observed.
[0262] 1: Less than 80% transfer was observed. (Worst)
[0263] 5) High light transfer
[0264] The above-mentioned printed matter (printed matter using PET film) was used for the fly-white test, and the circumference of the gravure was visually evaluated. The ratio of the area of white spots in the highlight printing part (dot area less than 10%) and the degree of contamination of the non-printing part when printing at a speed of 200 m / min. Rating 4 or above is in the practical range.
[0265] (Evaluation Criteria)
[0266] 5: There is absolutely no flying white and no pollution in non-printing areas.
[0267] 4: White spots are slightly observed, or stains are slightly observed in the non-printing area.
[0268] 3: White spots were slightly observed, and stains were slightly observed in the non-printed portion.
[0269] 2: White spots were observed, and stains were observed in non-printed portions.
[0270] 1: Many white spots were observed, and many stains were also observed in the non-printing part.
[0271] 6) Fog
[0272] Regarding the blur test, the degree of contamination (fogging) of the non-printed portion of the printed matter (printed matter using a PET film) was evaluated.
[0273] (Evaluation Criteria)
[0274] 5: No printing contamination is visible at all.
[0275] 4: It can be confirmed that printing contamination is minimal.
[0276] 3: Although printing contamination can be slightly observed, it is within the practical range.
[0277] 2: Printing contamination was significantly observed.
[0278] 1: Printing pollution is very obvious.
[0279] 7) Viscosity stability
[0280] The viscosity of the obtained printing ink immediately after the production (mixing) of the ink and the viscosity two weeks after the production (mixing) of the ink were measured using Zahn cup #3 (manufactured by Rigo Co., Ltd.), and the two values were compared.
[0281] 5: No viscosity change.
[0282] 4: Viscosity changes within 3 seconds.
[0283] 3: Viscosity change within 6 seconds.
[0284] 2: The viscosity change is 10 seconds or more.
[0285] 1: Viscosity change is 15 seconds or longer or gelation occurs.
[0286] [Examples 1 to 36, Comparative Examples 1 to 5]
[0287] Examples 1 to 36 were prepared according to the composition shown in Tables 1 to 6, and Comparative Examples 1 to 5 were prepared according to the composition shown in Table 7. Inks were prepared and evaluated in the same manner as in Example 1.
[0288] [Table 1]
[0289]
[0290] [Table 2]
[0291]
[0292] [Table 3]
[0293]
[0294] [Table 4]
[0295]
[0296] [Table 5]
[0297]
[0298] [Table 6]
[0299]
[0300] [Table 7]
[0301]
[0302] In the table, an isocyanate curing agent (BASONAT HB100, manufactured by BASF Corporation) was used as the curing agent.
[0303] In addition, polyethylene wax (S-394, manufactured by SHAMROCK CORPORATION) was used as the polyolefin wax.
[0304] According to the embodiments, the liquid ink of the present invention meets the required level in all the evaluation results and shows excellent performance. In the test of film adhesion, it can be seen that for various films of OPP film, PET film, and nylon film, excellent adhesion is shown in any film. In addition, the liquid ink of the present invention is low-viscosity, so when the viscosity is adjusted with a solvent during printing, the dilution solvent can be unnecessary or reduced, and the discharge of volatile organic compounds (VOC) can be reduced. In addition, since it can be used as a printing ink while maintaining a high pigment concentration, excellent printing adaptability can be achieved with a small coating amount.
[0305] The liquid ink composition for laminating flexible packages of the present invention exhibits high adhesion and anti-blocking properties even with various films and lamination methods. As a low-solvent-content and high-concentration liquid ink composition for laminating flexible packages, it can be widely used in various film compositions for industrial products such as food packaging materials, sanitary products, cosmetics, and electronic components.
Claims
1. A liquid ink composition comprising at least a binder resin and an organic solvent, wherein the binder resin comprises a polyester resin (A) having a number average molecular weight within a range of 500 to 20,000 and a chlorinated polyolefin resin (B).
2. The liquid ink composition according to claim 1, wherein The hydroxyl value of the polyester resin (A) is in the range of 10 to 150 mgKOH / g.
3. The liquid ink composition according to claim 1 or 2, wherein The chlorinated polyolefin resin (B) has a weight average molecular weight of 10,000 to 60,000 and a degree of chlorination of more than 10%. 4 . The liquid ink composition according to claim 1 , further comprising another resin having a glass transition temperature of 40° C. or higher.
5. The liquid ink composition according to claim 4, wherein The other resin having a glass transition temperature of 40° C. or higher is at least one selected from vinyl chloride-vinyl acetate copolymer resin, polyamide resin, acrylic resin, nitrocellulose, cellulose acetate propionate, cellulose acetate butyrate, ketone resin, and butyral resin.
6. The liquid ink composition according to claim 1 or 2, wherein: The polyester resin (A) is contained in an amount of 30% by mass or more in terms of solid content relative to 100% by mass of the resin solid content contained in the liquid ink composition.
7. The liquid ink composition according to claim 1 or 2, wherein: The solid content ratio of the polyester resin (A) to the chlorinated polyolefin (B) is in the range of 100:0.1 to 100:
30.
8. The liquid ink composition according to claim 1 or 2, further comprising wax and / or silica.
9. A printed matter obtained by printing the liquid ink composition according to claim 1 or 2. 10 . A laminate comprising the printed matter according to claim 9 .
Citation Information
Patent Citations
Binder for printing ink and printing ink
JP1999279472A